If it's not what You are looking for type in the equation solver your own equation and let us solve it.
38=2(p-31)
We move all terms to the left:
38-(2(p-31))=0
We calculate terms in parentheses: -(2(p-31)), so:We get rid of parentheses
2(p-31)
We multiply parentheses
2p-62
Back to the equation:
-(2p-62)
-2p+62+38=0
We add all the numbers together, and all the variables
-2p+100=0
We move all terms containing p to the left, all other terms to the right
-2p=-100
p=-100/-2
p=+50
| 56=12y+3 | | 3/5w-6=9 | | -25x=2x19 | | W{t}=12t-1;t=1/3 | | 10t=60. | | 2(m+3)=26 | | 7y-29=62 | | 13x+5=360 | | -53=-v/6 | | 5c-2=53 | | 11-53=4c+3c | | 3(x-4)+3=3 | | 9x^2−8x=9 | | y=-6/7-6 | | (7x+5)^2=16 | | (7x+5)^(2)=16 | | –8m+10=–9m+3 | | 2(d-46)=12 | | 2(d-46)=123 | | 10w+2+5w+22=w | | 5h+9=32. | | 3-6w=-45 | | -24m=-48 | | 8=-7/3k | | (x-1)^2-73=0 | | 10b=9b−9 | | 7=p-37/6 | | 6=6(x-1) | | y+18=20y-1 | | -6x10=-82 | | 27=3(2c+5) | | 4(r-77)=52 |